Elvis, Muminmuggar och andra ting: Den passionerade samlaren - Marander-Eklund, Lena; Bergman, Johan (Kulturella Perspektiv – Svensk etnologisk tidskrift, 2017)
In his definition of collecting, Russell W. Belk includes an element of passion. In this article, we try to examine how the passion in relation to collecting is to be understood. According to Robert J. Vallerand a passionate behavior originates from an autonomous activity of identity. This leads people to engage in an enjoyable activity, and results in a longing to feel connected or related to above-mentioned activity. Our analysis consists of three cases. Firstly, we look at an interview with a person who collects Elvis-memorabilia. Secondly, we analyze a questionnaire about collecting Moomin mugs and thirdly we examine presentations of collectors and collections in the magazine The Simple Things (2013–2015). Although the analyzed cases are rather diverse, they show the meaning stuff has in people’s lives as a way of making life worth living.